Prevalence and timing of prenatal ultrasound findings in cytomegalovirus‐infected pregnancies - Emma Van den Eede; Bart De Keersmaecker; Katrien Lagrou; Lennart Van der Veeken; Sanne Vanwinkel; Maja Vangoitsenhoven; Michael Aertsen; Luc De Catte (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction To investigate the prevalence and timing of prenatal neurosonographic abnormalities after primary cytomegalovirus seroconversion by the first trimester of pregnancy. The additional value of magnetic resonance imaging (MRI) and the correlation between cytomegalovirus viral load in amniotic fluid and adverse neonatal outcomes were evaluated. Material and Methods A retrospective study between 2006 and 2022 examined data from 440 women with amniocentesis for periconceptional and first‐trimester cytomegalovirus seroconversion. Cases with positive amniocentesis and subsequent follow‐up were included. Prenatal neurosonography, MRI, and clinical outcomes were analyzed. Results Out of 190 women included, 37% (n = 70) presented with a normal neurosonography. Patients exhibiting abnormal neurosonography findings showed higher viral loads in amniotic fluid compared to those with a normal neurosonography (p = 0.002). In 26% (n = 49) the first abnormal ultrasound sign was already picked up at amniocentesis, and the most common ones were echogenic bowels (49%) and periventricular echogenicity (43%). With increasing gestational age, the likelihood of a new abnormal neurosonography finding decreases. MRI discovered additional abnormalities in 14% (n = 10). Conclusions The results highlight the importance of combining diagnostic modalities, from amniocentesis to biweekly ultrasound monitoring and subsequent MRI evaluation, to capture the chronological progression and subsequent outcome of congenital cytomegalovirus.